O brincar de crianças de cinco e seis anos na escola: uma perspectiva walloniana - Cherubini, Carla Paola Freitas (2023)
This qualitative research aimed to investigate how playing occurs for five-and-six-year-old children at school. It was performed at a private school in the city of São Paulo and the theoretical framework used was wallonian psychogenetics. We selected a group of nine early education and first grade students, aged five and six, to observe their playtime moments at school, inside or out of the classroom. We elaborated charts and syntheses to organize data analysis and discussion. Data were produced by using: school documents, especially its Political Pedagogical Project, informal interviews with school administrators and teachers, and participant observation, whose data were registered in a field journal. This study showed the articulations between the psychological and the pedagogical dimensions of playing, revealing that intentionally planned directed playtime promotes children development as a whole, in their effective, intelligence and movement domains. It may also provide the onset of spontaneous, free playing, as long as teachers can acknowledge the importance of children’s full development within their teaching concepts, that playing is a core condition for learning and development, and that it take sensitive watching and listening, respecting children’s wishes, to bring flexibility to planning, which will allow children’s playing and expressing in its wholeness. Such process is possible because the teachers were and are continuously trained for pedagogical actions based on concepts of human and education that acknowledge the importance of students’ full development. We also observed that the body is considered a learning channel, and the movement domain is integrated with the effective and intelligence domains, which constitute children as a whole